Development of an effective tool for risk communication about food safety issues after the Fukushima nuclear accident: What should be considered?. (September 2017) - Cho, Tae Jin; Kim, Nam Hee; Hong, Yoon Ji; Park, ByoungIl; Kim, Hee Sung; Lee, Hyang Gi; Song, Min Kyung; Rhee, Min Suk
Abstract: Although the Fukushima nuclear accident (FNA) in 2011 led to strong public anxiety about radioactive contamination of foods, the most appropriate way to communicate this risk has been poorly researched. We sought to design, develop, evaluate, and optimize an effective risk communication (RC) tool for food consumers after the FNA. To design this tool, a classical systematic qualitative research framework that consisted of formative evaluation, development of a pilot RC tool, and outcome evaluation was applied. The formative evaluation consisted of focus group interview (FGI) with food consumers: its aim was to identify the major risk messages. Due to the low knowledge base of the food consumers and the absence of a credible existing information source, a pilot RC tool was developed. An educational book was selected as the most effective RC vehicle. The FGI results were reflected in the content of the book, which was presented in a 'frequently asked questions and answers' format. To ensure ready comprehensibility of the book, the scientific words were paraphrased and visual aids were employed. To ensure credibility of the RC, evidence supporting its statements was provided and it was made clear that the RC was a collaborative message from multiple risk communicators (consumer organizations, government bodies, and academia). Outcome evaluation with a consumer survey showed that the RC tool effectively increased the knowledge base of food consumers and relieved their anxieties. This study suggests that in the event of another nuclear accident, food safety RCs should meet the following key requirements: 1) the RC should send a clear message that reassures food consumers that the fatal risk is well controlled, which will reduce public fear and outrage; 2) the RC should improve the knowledge base of food consumers about food safety by providing appropriate education; and 3) the RC should be produced via multi-institutional cooperation so that the credibility of risk communicators is rebuilt. Our results may help the planning of an effective radiological RC strategy for food consumers, thereby preventing misunderstandings and relieving food consumers of unnecessarily severe anxiety. Highlights: After the accident, successful risk communication (RC) for food safety is limited. Systematic framework was adopted to develop and optimize RC tool for consumer. Educational book with evidential data and visual aids was selected as RC tool. Theme of book was 'Frequently asked question & answer' for two-way communication. The RC tool effectively improved consumers' knowledge and relieved their anxiety.